Implementation of PDCA Metacognitive Learning Strategies to Metacognitive Abilities, Science Process Skills, and Student Learning Outcomes - Yana Fajar Prakasa (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2023)
Students in class XI MIPA often have difficulty learning chemistry in acid and alkaline solutions because the learning process is dominated by lecture and rote learning. The use of PDCA metacognitive strategies (SM-PDCA) in the learning process can help students improve their metacognitive abilities to understand abstract concepts. This study aims to determine the implementation of learning, metacognitive abilities, science process skills, and cognitive learning outcomes of students in the SM-PDCA experimental class and expository control class (Ep), as well as the effect of applying learning. This study used a quasi-experimental design (Quasi Experiment Design) with Nonequivalent Control Group Design involving class XI MIPA as the experimental class and class XI MIPA as the control class. The results showed that: (1) the implementation of the learning process in the SM-PDCA class was 96.97% and the Ep class was 97.61% in the very good category; (2) the metacognitive abilities in the SM-PDCA class were in the high category 28.125%, while in the Ep class the high category was 6.25%, the science process skills in the SM-PDCA class were in the very high category 34.375%, while in the Ep class the category was very high 6.25 %, and the cognitive learning outcomes of students in SM-PDCA class with an average of 88.22 and Ep class of 77.64; (3) there is an effect of learning with SM-PDCA on metacognitive abilities, science process skills, and cognitive learning outcomes of students.